A simple approach for CTAB-free and biofunctionalized gold nanorods to construct photothermal active nanomedicine for potential in vivo applications in cancer cells and scar treatment - Foti, Alice; Clépoint, Benjamin; Fraix, Aurore; D’Urso, Luisa; De Bonis, Angela; Satriano, Cristina (Frontiers in Materials, 2024)
Cetyltrimethylammonium bromide (CTAB), a commonly used surfactant in the synthesis of gold nanorods (AuNR), presents cytotoxicity challenges in biological applications, limiting their biomedical applicability, particularly in cancer therapy. This study introduces a straightforward methodology for the effective removal of CTAB by utilizing a combination of ligand replacement and surface bioconjugation processes that efficiently eliminates CTAB and simultaneously functionalizes the nanorods with hyaluronic acid (HA), to enhance biocompatibility and introduce targeting capabilities towards cancer cells. The surface chemistry modification of CTAB-capped and CTAB-free AuNR, before and after the functionalization with HA, was scrutinized by UV-visible, surface-enhanced Raman scattering (SERS), attenuated total reflectance (ATR) Fourier transform infrared (FTIR), and X-Ray Photoelectron (XPS) spectroscopies. The surface charge, size and morphology of the different plasmonic nanoparticles were characterized by zeta potential, dynamic light scattering, and transmission electron microscopy (TEM). The photothermal response was assessed by laser irradiation and thermocamera measurements. Proof-of-work in vitro cellular experiments of cytotoxicity and oxidative stress were carried out on prostate cancer cells, PC-3, overexpressing the CD44 cell surface receptor specifically recognized by HA, in the comparison with the CD44-negative murine fibroblasts (3T3 cell line) by MTT and MitoSOX assays, respectively. The cellular uptake and the organelle alteration were scrutinized by confocal laser scanning microscopy (LSM), while the perturbative effects on cell migration were studied by optical microscopy (wound scratch assay). The study's findings offer a promising pathway to tune the gold nanorods properties in cancer treatment by reducing cytotoxicity and enhancing targeted therapeutic efficacy as well as in the control of scar tissue formation.